IBM Akupresure untuk Mengatasi Dismenore pada Remaja Putri - Martin, Novia; Hambami, Sarifah; Rahmawati, Rahmawati; Fitri, Juli; Triani, Evina; Isfaizah, Isfaizah; Widyaningsih, Ari (UNIVERSITAS NGUDI WALUYO, 2021)
Dysmenorrhea is menstruation accompanied by pain and is often complained of 40-80% of young women. Dysmenorrhea occurs because the endometrium in the secretion phase produces excessive prostaglandins that cause hypertonus and vasocontction of the myometrium resulting in ischemia, endometrial disintegration, bleeding, and pain. Dysmenorrhea can be treated by administering pharmacological therapy with non-steroidal and non-pharmacological anti-inflammatory drugs with acupressure techniques.Acupressure is done by massaging techniques at certain meridian points of the body to stimulate the natural ability to heal yourself by restoring a positive energy balance in the body. This community service aims to provide information about acupressure to reduce dysmenorrhea in young women online through zoom meetings with powerpoint slideshows and videos.The steps are the selection of groups of adolescents who are willing to be taught about acupressure to reduce dysmenorrhea pain, counseling and acupressure training and evaluation using google form. The service was conducted online on June 20, 2021 at 08.00-10.00 WIB which was attended by 30 young women in D.I Yogyakarta, Jambi, East Java, Lampung, South Sumatra, and Southeast Sulawesi.The results were an increase in the level of knowledge and skills of young women before and after counseling on acupressure to overcome dysmenorrhea. Before counseling, the level of adolescent knowledge is less, then after counseling the level of adolescent knowledge becomes sufficient and good. The need for various activities that improve the health of adolescents online in this pandemic.ABSTRAKDismenore adalah menstruasi yang disertai nyeri dan sering dikeluhkan 40-80% wanita muda.Dismenore terjadi karena endometrium dalam fase sekresi memproduksi prostaglandin berlebihan yang menyebabkan hipertonus dan vasokontriksi pada miometrium sehingga mengakibatkan iskemia, disintegrasi endometrium, perdarahan, dan nyeri.Dismenore dapat ditangani dengan pemberian terapi farmakologi dengan obat-obatan anti inflamasi non-steroiddan non farmakologidengan teknik akupresur.Akupresur dilakukan dengan teknik memijat pada titik meridian tubuh tertentu untuk merangsang kemampuan alami menyembuhkan diri sendiri dengan mengembalikan keseimbangan energi positif dalam tubuh.Pengabdian masyarakat ini bertujuan untuk memberikan informasi tentang akupresure untuk mengurangi dismenore pada remaja putri secara daringmelalui zoom meetingdengan slideshow powerpointserta video. Adapun langkah-langkahnya adalah pemilihan kelompok remaja yang bersedia diajarkan tentang akupresure mengurangi nyeri dismenorea, penyuluhan dan pelatihan akupresure serta evaluasi menggunakan google form.Pengabdian dilakukan secara daring pada tanggal 20 Juni 2021 pukul 08.00-10.00 WIB yang diikuti oleh 30 remaja putri di D.I Yogyakarta, Jambi, Jawa Timur, Lampung, Sumatera Selatan, dan Sulawesi Tenggara. Hasil terdapat peningkatan tingkat pengetahuan dan keterampilan remaja putri sebelum dan sesudah diberikan penyuluhan tentang akupresure untuk mengatasi dismenorea.Sebelum dilakukan penyuluhan, tingkat pengetahuan remaja adalah kurang, kemudian setelah dilakukan penyuluhan tingkat pengetahuan remaja menjadi cukup dan baik.Perlunya berbagai kegiatan yang meningkatkan derajat kesehatan remaja secara daring dimasa pandemi ini.